1984
DOI: 10.1207/s15328023top1102_3
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions about Psychology Aren't Always What They Seem

Abstract: These nine often researched misconceptions appear to be candidates for qualification or at least a caution in interpretation.Studies showing .that beginning psychology students enter the classroom with misconceptions about the subject matter can only confirm what most teachers of psychology already know (e.g., Brown, 1983;Vaughan, 1977). What is perhaps surprising, or at least disconcerting, is evidence that the introductory course is not very successful at dispelling the misconceptions (Lamal, 1978;Gutman, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…This could be a problem, as knowledge in different scientific areas evolves quickly and therefore may not be captured in textbooks (Buskist, Miller, Ecott, & Critchfield, 1999). However, Brown (1984) and Barnett (1986) have pointed out that because psychology is so complex, simple statements are sometimes difficult to compose. For example, Lamal (1979) found that instructors disagreed with several of the questions.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a problem, as knowledge in different scientific areas evolves quickly and therefore may not be captured in textbooks (Buskist, Miller, Ecott, & Critchfield, 1999). However, Brown (1984) and Barnett (1986) have pointed out that because psychology is so complex, simple statements are sometimes difficult to compose. For example, Lamal (1979) found that instructors disagreed with several of the questions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ambiguity inherent in asking students to assess simple true/false statements about complex psychological issues, previous studies on psychological misconceptions have mostly speculated on the sources of misconceptions and have recommended that research assess the sources of misconceptions (Barnett, 1986;Brown, 1984;Griggs & Ransdell, 1987;Higbee & Clay, 1998;McCutcheon, 1991;Panek, 1982;Ruble, 1986;Vaughn , 1977). Only the source of prior belief in the 10% myth has been investigated to any great extent (Higbee & Clay, 1998).…”
mentioning
confidence: 99%
“…Sometimes the qu~estions used in these studies are ambiguous. Brown (1984) examined nine of the questions used in tests to identify misconceptions and found that the "correct" answers were misleading. Brown concluded that because the find--ings of psychology are complex, they frequently cannot be summarized in simple, objective statements.…”
mentioning
confidence: 99%